PENDIDIKAN KARAKTER DI MADRASAH ALIYAH NEGERI (MAN) 2 BANJARMASIN - Burhanuddin Abdullah; Radiansyah Radiansyah; Ali Akbar (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The purpose of this study was to determine the role and responsibilities of teachers in implementing character building in Madrasah Aliyah Negeri 2 Banjarmasin. This study is a field research (field research) using descriptive qualitative approach.The population consisted of all teachers Madrasah Aliyah Negeri 2 Banjarmasin 62 people, and the sample 29 teachers in class XI. Methods of data collection in this study used the method of observation, interviews and documentation. The research result is the existence of sufficient learning facilities, extra-curricular activities. The participation of teachers in routine activities is required such as the implementation of the prayers in the mosque and spontaneous activities, such as giving sanction tostudents who are late, make slogans that can affect students for good character.